The Expression of Petunia Strigolactone Pathway Genes is Altered as Part of the Endogenous Developmental Program - Drummond, Revel S.; Sheehan, Hester; Simons, Joanne L.; Martínez-Sánchez, N M.; Turner, Rebecca M.; Putterill, Joanna; Snowden, Kimberley C. (Frontiers in Plant Science, 2012)
Analysis of mutants with increased branching has revealed the strigolactone synthesis/perception pathway which regulates branching in plants. However, whether variation in this well conserved developmental signalling system contributes to the unique plant architectures of different species is yet to be determined. We examined petunia orthologues of the Arabidopsis MAX1 and MAX2 genes to characterise their role in petunia architecture. A single orthologue of MAX1, PhMAX1 which encodes a cytochrome P450, was identified and was able to complement the max1 mutant of Arabidopsis. Petunia has two copies of the MAX2 gene, PhMAX2A and PhMAX2B which encode F-Box proteins. Differences in the transcript levels of these two MAX2-like genes suggest diverging functions. Unlike PhMAX2B, PhMAX2A mRNA levels increase as leaves age. Nonetheless, this gene functionally complements the Arabidopsis max2 mutant indicating that the biochemical activity of the PhMAX2A protein is not significantly different from MAX2. The expression of the petunia strigolactone pathway genes (PhCCD7, PhCCD8, PhMAX1, PhMAX2A, and PhMAX2B) was then further investigated throughout the development of wild-type petunia plants. Three of these genes showed changes in mRNA levels over the development series. Alterations to the expression of these genes over time, or in different regions of the plant, may influence the branching growth habit of the plant. Alterations to strigolactone production and/or sensitivity could allow both subtle and dramatic changes to branching within and between species.